Thermal analysis of Al2O3/water nanofluid-filled micro heat pipes. Issue 34 (15th April 2015) - Gan, Jie Sheng; Hung, Yew Mun
<x xml:space="preserve">Abstract</x> The comparison of heat transport capacity and the thermal resistance as the performance indicators provides valuable insights into the underlying physical significance of the use of a nanofluid on the performance of micro heat pipes.